DEVELOPING METACOGNITIVE AWARENESS READING QUESTIONNAIRE (MARQ) FOR READING COMPREHENSION; A PRELIMINARY STUDY - Dwi Indra Aprilliandari; Rindu Handayani (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This initial study seeks to create a Metacognitive understanding Reading Questionnaire (MARQ) to evaluate university students' understanding of metacognitive methods in reading comprehension. The MARQ emphasises critical tactics including preparation, monitoring, and evaluation, which are vital for enhancing reading comprehension, especially in academic and assessment environments such as the TOEFL. The study used a qualitative method to assess the initial usefulness of the MARQ, highlighting its potential to guide treatments and improve students' metacognitive awareness and reading ability. Three experts were asked to validate the questionnaire; one expert to validate a construct validation sheet and two experts to validate the content validity sheet. The statements in validation sheets used a Likert-scale from a range of Strongly Agree and Strongly Disagree. The results from the experts were then described in percentages to obtain the validity and reliability of the questionnaire. It is recommended that the tool undergo more improvement for wider use. Integrating metacognitive strategy training into the academic curriculum may augment learning results, enhance reading efficiency, and elevate overall performance in high-stakes reading assessments.